PENGARUH SUHU PENGERINGAN TERHADAP KADAR FLAVONOID EKSTRAK ETANOL DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Yuska Noviyanty; Oktri Wardania; Hepiyansori Hepiyansori (Oceana Biomedicina Journal, 2023)
Introduction : Binahong leaf (Anredera cordifolia (Ten.) Steenis) is one of the plants that is empirically used to treat various diseases. And contains many secondary metabolites, one of which is flavonoid compounds. Binahong leaf (Anredera cordifolia (Ten.) Steenis) has bioactivity as an antioxidant, antibacterial, antifungal, antidiabetic, anti-inflammatory, antiseptic, and antibacterial contains many secondary metabolites, one of which is flavonoid compounds. Methodes: The leaves used were processed into simplicia by oven heating method with different temperature variations (35OC, 50OC, 65OC) and extracted using 70% ethanol solvent. Furthermore, the identification of flavonoid compounds with the addition of concentrated Mg and HCl powder which is positive for flavonoids if the color is yellow-orange. The determination of the levels of flavonoid compounds was carried out using the UV-Vis spectrophotometric method. Results: Identification tests that have been carried out with ethanol extract of Binahong (Anredera cordifolia (Ten.) Steenis) leaves at 35OC, 50OC, and 65OC positive contain flavonoids seen from the color produced, which is yellow-orange. And the average levels of flavonoids obtained at a temperature of 35oC: 2.685% 50oC: 2.476% and 65oC: 1.980%. Conclusion : The lower the drying temperature of the simplicia, the higher the levels of flavanoid compounds. Variations in simplicia drying temperature had no effect on the presence of flavanoid compounds.